The JFK conspiracy [large type] : the secret plot to kill Kennedy--and why it failed - Meltzer, Brad; Mensch, Josh (Thorndike Press large print nonfiction series., 2025)
"Most Americans don't know is that JFK's presidency almost ended before it began. On December 11, 1960, shortly before Kennedy's inauguration, a retired postal worker named Richard Pavlick waited in his car on a quiet street in Palm Beach, Florida. Pavlick knew when Kennedy would leave his house. He knew where Kennedy was going. From there, Pavlick had a simple plan--one that could've changed the course of history. Written in the gripping, page-turning style that is the hallmark of Brad Meltzer and Josh Mensch's bestselling series, this is a slice of history vividly brought to life"--